The Impact of Employing Artificial Intelligence on Public Utility Services - Ekhlas Abarahim Khalf Ebrahim Alzubaydi (Procedia of Social Sciences and Humanities, 2025)
The use of AI technologies is introducing a dramatic change to public utilities because of the widening application in many aspects of administration and services. This change has had direct impact on the quality of services delivered to the people in the form of speed, accuracy and delivery mechanisms, and has also altered the arrangement of relationship between the administration and the service beneficiaries. The provision of public services is no longer conducted as a conventional input based on the manual process; it is becoming more and more dependent on the smart system that can process and analyze the information and make the decision or suggest the solution automatically or semi-automatically. Against this backdrop, several implications of using artificial intelligence in public utilities have been identified be it in the nature of enhancing efficiency and the quality of performance, or the legal and regulatory concerns that it can present in respect to accountability, transparency as well as safeguarding rights. Therefore, AI has assumed one of the leading roles in the creation of the public services and in the reconstruction of the law concerning the functioning of the public utilities in Iraq.